The Politics of Costa Rica - Petri, Dennis P. author. aut Link
XVI, 223 p. 48 illus., 41 illus. in color.
Keywords: This textbook provides a comprehensive overview of the Costa Rican political system. It covers political history, the government system and its elements (political regime, electoral system, party system), political institutions (four branches: executive, legislative, judiciary and electoral) and includes an in-depth analyses of a selection of policy fields: economic development policy, health policy, education policy, security policy, environmental policy, and religious policy. This textbook is intended for upper undergraduate and graduate courses in the Costa Rican political system and includes lecture slides and discussion questions for instructors.